The impact of iron limitation on the physiology of the Antarctic diatom Chaetoceros simplex - Petrou, K; Trimborn, S; Rost, B; Ralph, PJ; Hassler, CS (2014)
Iron availability strongly governs the growth of Southern Ocean phytoplankton. To investigate how iron limitation affects photosynthesis as well as the uptake of carbon and iron in the Antarctic diatom Chaetoceros simplex, a combination of chlorophyll a fluorescence measurements and radiotracer incubations in the presence and absence of chemical inhibitors was conducted. Iron limitation in C. simplex led to a decline in growth rates, photochemical efficiency and structural changes in photosystem II (PSII), including a reorganisation of photosynthetic units in PSII and an increase in size of the functional absorption cross section of PSII. Iron-limited cells further exhibited a reduced plastoquinone pool and decreased photosynthetic electron transport rate, while non-photochemical quenching and relative xanthophyll pigment content were strongly increased, suggesting a photoprotective response. Additionally, iron limitation resulted in a strong decline in carbon fixation and thus the particulate organic carbon quotas. Inhibitor studies demonstrated that, independent of the iron supply, carbon fixation was dependent on internal, but not on extracellular carbonic anhydrase activity. Orthovanadate more strongly inhibited iron uptake in iron-limited cells, indicating that P-type ATPase transporters are involved in iron uptake. The stronger reduction in iron uptake by ascorbate in iron-limited cells suggests that the re-oxidation of iron is required before it can be taken up and further supports the presence of a high-affinity iron transport pathway. The measured changes to photosystem architecture and shifts in carbon and iron uptake strategies in C. simplex as a result of iron limitation provide evidence for a complex interaction of these processes to balance the iron requirements for photosynthesis and carbon demand for sustained growth in iron-limited waters. © 2014 The Author(s).